Arab spring and Middle East democratization: issues and challenges - Zakaria, Sultan Mohammed (© 2015 Ashgate Publishing Ltd, 2016)
This book chapter was published in Non-Western Encounters with Democratization: Imagining Democracy after the Arab Spring [© 2015 Ashgate Publishing Ltd.]